IBN SINA'S THOUGHTS RELATED TO ISLAMIC EDUCATION - Yulita Putri; Abid Nurhuda (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2023)
Education can be seen from two dimensions, namely practice and theory where both are interdependent in forming a systemic concept. Even so, the existing system in national education today adopts more western theory than Islamic theory itself which is often ignored. Therefore the purpose of this study is to describe Ibn Sina's thoughts regarding Islamic education. The method used is descriptive qualitative with a literature study approach, after the data has been collected it is analyzed for its contents and then concluded. The results of the study show that Ibn Sina's thoughts regarding Islamic education include aspects of the human psychology consisting of the souls of plants, animals and humanity as subjects and objects involved in it. In addition, it also emphasizes the importance of educational goals that contain directions, stimuli and values. Then the preparation of a curriculum that considers various aspects, there are also various methods to suit the situation and conditions. Lastly is the concept of students who have potential and the concept of competent educators.